Commitment and the emigration intentions of South African professional nurses - Jeffrey J. Bagraim (AOSIS, 2013)
The emigration of skilled nurses from South Africa exacerbates the crisis in the provision of public health services. A descriptive, quantitative design was applied to investigate the relationship between intention to emigrate and employee commitment. Over 400 registered nurses (N = 419), working within public sector tertiary hospitals in the Western Cape, responded to a cross-sectional survey questionnaire. Three foci of employee commitment (organisational, professional and national) were examined but only national commitment significantly helped predict intention to emigrate from South Africa in the regression model (beta = -0.0525, p < 0.0001). The implications of the results obtained in this study are discussed. Die emigrasie van verpleegkundiges uit Suid-Afrika vererger die krisis in die verskaffing van gesondheidsorgdienste in die land. 'n Beskrywende, kwantitatiewe ontwerp is gebruik om die verwantskap tussen werknemertoewyding en die voorneme om te emigreer te ondersoek. Meer as 400 verpleegsters (N = 419) wat in openbare tersiêre hospitale in die Wes-Kaap werk, het op die vraelys gereageer. Drie fokusareas van toewyding (organisatories, professioneel en nasionaal) is gemeet, maar net nasionale toewyding het daartoe bygedra om emigrasievoorneme te voorspel (beta = -0.0525, p < 0.0001). Die implikasies van hierdie resultate word bespreek.